In-Silico Analysis And Molecular Dynamics Simulation Analysis of Sida rhombifolia Compounds as Candidate Antibacterial Agents Against Methicillin-Resistant Staphylococcus aureus - alshol firdaus; Rina Herowati; Ismi Rahmawati; Andri Prasetiyo; Herman Herman (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Antibiotic resistance has become a critical issue in global health, one of which is MRSA. The dynamic problem related to the increasing MRSA infections is clear evidence that the treatment and management of this disease have not been optimally resolved, requiring the development of effective antimicrobial agents against MRSA. An exploratory method was used to assess the antibacterial activity, interaction patterns, and stability of sidaguri compounds. A total of 15 potential compounds from sidaguri were docked onto four molecular targets: PBP2a (4JCN), MecR1 (609S), FtsZ (8HTB), and SCCmec (4FAK), using the molecular docking methods AutodockTools and PyMol, followed by analysis of the amino acid residue similarity of each test ligand. The molecular docking results predicted that the compounds with the best binding affinity and interaction patterns similar to the natural ligand for their respective molecular targets were quercetin, ecdysone, and 24-methylenecholesterol. The validation parameters are calculated from RMSD and RMSF based on the In-Silico predictions. MD simulations were performed using YASARA Dynamics. The MD simulation results showed that, from the RMSD and RMSF graphs of the MRSA target molecules, quercetin, ecdysone, and 24-methylenecholesterol exhibited binding stability close to that of the natural ligand. The predicted pharmacokinetic profiles show that all three compounds have a good ADMET profile, with optimal absorption potential, adequate distribution, appropriate metabolism, and relatively low toxicity, making them promising candidates for development as antibacterial drugs against MRSA